Pengaruh Envionmental, Social, Governance (ESG) Disclosure terhadap Nilai Perusahaan Sektor Energi pada Tahun 2020-2024 - Mohammad Rafli Putera Fadhlyta; Willy Sri Yuliandhari (Jurnal Riset Akuntansi, 2026)
This research investigates the link between ESG disclosure and firm value within energy companies, incorporating firm size, profitability, and leverage as control variables to improve the precision of the estimates. A quantitative causal research design is employed, relying on secondary data drawn from the annual and sustainability reports of energy-sector companies listed on the Indonesia Stock Exchange across 2020 to 2024. The sample was determined via purposive sampling, and panel data regression served as the analytical technique, preceded by descriptive statistics, classical assumption tests, and selection of the optimal regression model. The results indicate that ESG disclosure does influence firm value, although the magnitude of this influence varies according to each company’s conditions and the extent of its disclosure. Larger company size and higher profitability tend to raise firm value, while leverage shows inconsistent results linked to each firm’s risk exposure. This study contributes to the body of literature concerning the relationship between ESG and firm value, particularly within the energy industry. Its findings may guide corporate management in enhancing the quality of ESG disclosure and assist investors in making more informed investment choices. Future research is encouraged to incorporate further variables, such as governance quality and macroeconomic indicators, to produce a more comprehensive understanding.